Development of a Method through Digital Image Analysis for Analyzing Polyaniline Based Sensors for Total Volatile Basic Nitrogen (TVBN) as Fish Freshness Indicators - Manna Joanna Maravillas; Althea Mae Mendenilla; Adrian Fernando Merino; Edna Quinto (ASEAN Journal of Chemical Engineering, 2019)
Food spoilage is a prevailing issue to society. This study addresses it by developing a freshness indicator using polyaniline through digital image analysis that monitors the condition of fish, which release amine vapors upon spoilage. The Polyaniline film prepared is analyzed through its digital image captured by a smartphone camera. The images’ RGB values were measured through the use of ImageJ Software. The RGB values are dependent on the film’s color, which reflects the effect of trimethylamine exposure. This study includes film preparation, analysis of the film’s RGB values upon exposure to trimethylamine standard and headspace of a real sample, and the results’ comparison with the UV-Vis Spectrophotometry’s. Results are: Blue color value signal stability: 1.72% RSD, Repeatability test RSD: 35.68%, Blue value LOD: 0.01384M, Blue color value sensitivity: 248.87 color value change/molar concentration with linear coefficient of R²=0.97391. Spectrophotometry’s results were more accurate as expected. Nevertheless, determination through RGB values produced acceptable results. However, data acquisition for the ImageJ software application, the configuration of the optical system, and data treatment can still be improved. The method showed promising results for detecting volatile nitrogen samples such as amines in fish samples as they begin to spoil, using a smart phone.